Art of the twentieth century and beyond movements, theories, schools, and tendencies - Parmesani, Loredana (Skira, 2012)
Following an analysis of the theories and poetics that traversed the historical avant-gardes and the neo-avant-gardes of the twentieth century, the author explains the principal artistic phenomena that starting in 1980, marked the period defined as post-modern, which was characterised by performance and a system of economic-financial art.